Ensaio randomizado, duplo-cego e controlado de anestesia tópica induzida por iontoforese de lidocaína - Schmitt, Juliano Vilaverde [UNESP]; Miot, Hélio Amante [UNESP] (My University, 2009)
Introduction: Needle infi ltration of local anesthetic is a painful procedure, thus, a topical anesthetic is a comfortable alternative; however, it is diffi cult to deliver transcutaneous polar drugs. Iontophoresis is a noninvasive technique that uses electrical current for releasing electrically charged drugs through biological membranes. Objective: To evaluate the anesthesia induced by iontophoresis of lidocaine for a standardized painful stimulus. Material and methods: Randomized, controlled, double-blind study, involving 10 volunteers under the anesthetic effects of topical application of lidocaine gel 2% and noradrenaline 1:50,000, with or without iontophoresis of 1.85 milliamps for 13 minutes. Pain sensitivity was evaluated by the prick of a 21G needle in the arms posterior region, using a visual numerical scale. Results: Patients mean age was 50.8 ± 11.4 years. Nine of them were women. All had previously received infi ltrative anesthesia. Iontophoresis was well tolerated by volunteers. The median pain scores were 0 and 3 for the arm that received the iontophoresis and for the one that did not receive, respectively (p < 0.01). Conclusion: The anesthetic effect in the region subjected to iontophoresis suggests an effi cient and comfortable method for promoting local anesthesia in the surgical approach of pediatric, hyperalgic, or needlephobic patients.
Randomized, double-blind, controlled topical anesthesia induced by iontophoresis of lidocaine
Keywords: Ambulatory surgery procedures; Anesthesia; Iontophoresis; Lidocaine